Organiziranost izobraževalnega sistema kot dejavnik integracije mladih na trg delovne sile - Ivančič, Angela (Družboslovne razprave, 2008)
Recent comparative studies of labour market entries and transitions from education to employment assert that in industrial countries individual resources play a significant role in the processes of allocation to jobs and labour market positions. However, differences exist among countries as to how this role is displayed. These differences and commonalities indicate that transitions from education to work and their outcomes in the labour market are embedded within specific institutional contexts and hence there is a need for institutional explanations to be taken into account in their research. The characteristics of education systems and the links between jobs and educational qualifications in conjunction with labour force protection and social welfare systems are considered by various scholars as the most clearly visible institutional factors affecting differences among countries in the links between education and employment and, above all, in patterns of transitions from schooling to employment. Given certain research findings the following dimensions are the most important in this respect: the scope of opportunities provided on different levels of education systems; the relative advantages of education systems mainly providing general qualifications over those delivering occupation-specific skills; the mode of organisation of the vocational education (the school form, vs. the dual form); the sorting of students in their early educational career on different tracks of curricula and with different educational requirements; the extent to which students encounter various obstacles in their progress up to the highest levels of education; the flexibility of educational links and the level of standardisation of educational programmes.
Keywords: Izobraževalni sistemi; Educational systems; Izobraževanje; Education; Zaposlovanje; Employment; Labor market; Trg dela; Mladi odrasli; Young adults; trg delovne sile; mladi; kariera; Kariera people